Genetic diversity, correlation and path analysis in female palmyrah (Borassus flabellifer L.) germplasm- a research article - Premalakshmi, V; Vasanth, S; Juliet, S H; Manivannan, M I; Nandhini, M (Plant Science Today, 2025)
In this study, 16 female germplasm of palmyrah were analysed to assess diversity among the accessions. The experiments were laid in Randomized Block Design with 2 replications. Around 27 characters were observed during the research, and they were subjected to correlation analysis, path analysis and genetic divergence. The results of the statistical analysis revealed the characters such as the number of leaves per tree, petiole length, number of inflorescences per tree, number of branches per inflorescence, number of fruit bunches per tree and number of fruits per bunch showed significant and positive correlations with fruit yield per tree. The path analysis showed, the traits viz., crown length (0.040), number of leaf segments per leaf (0.795), leaf length (0.845), inflorescence length (0.366), number of fruit bunches per tree (0.687), potassium (0.850), Total Soluble Solids (0.368), fruit length (0.230) and number of branches per inflorescence (0.170), petiole length (0.006), potassium content (0.850), phosphorous content (0.026) and calcium content (0.042) showed high positive direct effect with fruit yield per tree in female germplasm. In the genetic diversity analysis, the 16 germplasm were grouped into 12 clusters. The highest inter cluster distance was noticed between cluster VIII and cluster XI (959.377). The cluster VIII (Acc.11-KP-KKM) and cluster XI (Acc.2-OD -KKM) were showed high genetic divergence and utilized in the hybridization programme for developing superior genotypes with enhanced quality and improved yield. Among the various character studied, the maximum contribution to divergence was observed for zinc followed by number of fruits per bunch, fruit length, calcium and fruit weight.